The Theological-Spiritual Sense of the Principle and Foundation at the Different Stages of the Spiritual Exercises of Saint Ignatius of Loyola - Wacław Królikowski (Verbum Vitae)
The Spiritual Exercises of Saint Ignatius of Loyola have been famous in the Church for almost five centuries for their extraordinary effectiveness in building and deepening one’s relationship with God. This effectiveness is attributable not so much to their content, which is related to the fundamental truths of the faith of the Catholic Church and to the contemplation of the mysteries of the life of Jesus Christ, as to their precise method. The author of the Spiritual Exercises, by adapting their content to the exercitant, helps them to open themselves more and more to the action of the Lord God and to cooperate with him, so that he may ultimately love him in everything and serve his Divine Majesty. This final chord of man’s spiritual union with God is already present, as it were, in embryo in the first exercise of the Ignatian retreat, in the so-called Principle and Foundation (Principio y Fundamento). This exercise, commonly known as the Foundation, is, as it were, the root of the whole tree of spiritual development contained in the Spiritual Exercises. This is because the content of the Principle and Foundation develops and deepens more and more during the different stages of the Spiritual Exercises. The purpose of this article is to analyze scientifically the content of the Principle and Foundation and to show the theological-spiritual sense of the Principle and Foundation in the different stages of the Spiritual Exercises of St. Ignatius of Loyola. The text uses the method of analysis of the source texts and the literature on the subject, as well as the hermeneutical method, and shows that the synthesis of the spiritual life contained in the Ignatian Principle and Foundation continually develops and reaches its culmination in the last spiritual exercise of the Ignatian retreat – in the so-called “Contemplation to attain the love of God” (Ad amorem). In conclusion, it is shown that the content of the Principle and Foundation constitutes the foundations of the spiritual life, which, on the path of development, leads the exercitant to be able to “in all things love and serve the Divine Majesty.” (SE 233)